Developing The Voluntary Taxpayer Compliance: The Scale of The Tax Authority’s Power, Trust and The Fairness of The Tax System - Atik Djajanti (School of Business, IPB University (SB-IPB), 2020)
This study aims to analyze the scale of the power of the tax authority, trust and the fairness of the tax system for the voluntary compliance of the individual taxpayers who have businesses. The study was conducted in Jakarta and its surroundings, considering tax revenue in this region is the best compared to revenue in other regions in Indonesia. This research was a survey research. Convenience sampling method is used due to limitations in accessing individual taxpayer data. Personal data information in the tax authority was confidential. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results of the study showed that the scale of the power of the tax authority and the trust proved to have a positive effect on the voluntary tax compliance while the fairness of the tax system had a negative effect. The results of this study support the development of the slippery slope theory which was the novelty of this study. The scale of the power of the tax authority, which is a part of the tax authority, is generally a determinant of the enforced tax compliance. But this study proves that it is also needed to the voluntary tax compliance. Keywords: slippery slope theory, individual taxpayer, voluntary tax compliance, enforced tax compliance, PLS-SEM